PENGELOLAAN RETRIBUSI TEMPAT REKREASI TAMAN PURBAKALA BATU PAKE GOJENG DIKABUPATEN SINJAI - Irmawati Irmawati; Muhlis Madani; Anwar Parawangi (Kolaborasi : Jurnal Administrasi Publik, 2019)
The purpose of this researct was to know how to manage retribution of batu Pake Gojeng Archaeologi Park recreation area in sinjai regency, and the extent of influence caused by the management of retribution in Batu Pake Gojeng Archaeological Park. The type of research was qualitative. This research used descriptive qualitative and phenomenology with 9 informants. Data collection techniques such as interviews, observation and documentation. The results of this study indicated that the management of retribution in the Batu Pake Gojeng Archaelogical Park already quite maximum. It could be seen from the realization of the target amount of retribution from 2012 to 2016 always increased every year. The effect of retribution management of Batu Pake Gojeng Archaelogical Park recreation area in Sinjai regency was to increase visitor and increase local revenue in Sinjai regency.